Geography of the Inuit Food System in Nunavik : from the land to the Supermarket - Lamalice, Annie (CCSD, 2019)
The main objective of this thesis is the characterization and analysis of the transformations of the Nunavik Inuit food system, and particularly the issues raised at the intersection of human-environment interactions and their consequences for Inuit health and well-being. Possible solutions to improve the resilience of the food system in this northern region are explored, the main one being the development of community gardening projects. The collection of data to complete the four articles that make up the body of this thesis took place between October 2015 and March 2019 in the northern villages of Kuujjuaq and Kangiqsujuaq, Nunavik. This research combines different methods, the main one being based on the principles of participatory action research. The results illustrate that traditional foods from hunting, fishing and gathering activities continue to be important drivers of Inuit’s well-being and relationship to the land, despite the fact that they are now consumed in smaller quantities. The loss of mobility and the adoption of a new way of life, accompanied and made possible by the nutritional transition, have disrupted human-environment interactions at different levels. The greatest pressure on the natural environment comes from human activities elsewhere in the world and from a pattern of inconsistent consumption that generates many negative externalities on the environment and human health. Through the food they eat, the Inuit are now connected to the rest of the world through the globalized food system, the complex ramifications of which cover the entire planet. In Nunavik, the defects inherent in the global agri-food production chain are expressed in a very singular way. The intensification of the links between the Inuit economy and the globalized economy contributes to placing the northern territories in a position of unequal exchange and dependence on the producers and suppliers of an exogenous agri-food sector in which northern residents have few opportunities to be heard. Food sovereignty over ...